Інформаційна технологія вибору методу оцінки ефективності роботи персоналу на підприємстві - Хімій, М. В. (ХНУРЕ, 2025)
This work presents the development of a module for evaluating employee performance. The study explores key performance indicators (KPIs), descriptive statistics, and productivІТy assessment methods. Descriptive statistics provide a comprehensive overview of employee performance trends, while KPI analysis allows for targeted performance improvement. The module integrates advanced data analytics to facilІТate informed decision-making and enhance operational efficiency.
Keywords: персонал; оцінка ефективності роботи персоналу